2014
DOI: 10.1159/000364875
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Three Tracheal Intubation Techniques in Thyroid Tumor Patients with a Difficult Airway: A Randomized Controlled Trial

Abstract: Objective: To investigate the effectiveness of the Shikani optical stylet (SOS) and GlideScope video laryngoscope (GVL) for tracheal intubation of thyroid tumor patients with a difficult airway. Subjects and Methods: One hundred and twenty thyroid tumor patients with a difficult airway, who were undergoing elective surgery requiring general anesthesia, were enrolled in the study. They were randomly allocated to 3 groups (n = 40 each) who underwent direct laryngoscopy (DL), SOS or GVL. The outcomes recorded wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 20 publications
2
19
1
1
Order By: Relevance
“…Previous studies showed the lowest incidence of lip and mucosal trauma with SOS compared with MLS and Glidescope. [ 6 14 ] However, in the study, only three patients in MLS group and one in SOS group had evidence of small lacerations on the lip or oral mucosa. None of the four patients required further treatment, and all resolved within 24 h. These results might be related to the Cormack-Lehane classification applied in all patients before undergoing intubation and the extensive experience of the operator.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…Previous studies showed the lowest incidence of lip and mucosal trauma with SOS compared with MLS and Glidescope. [ 6 14 ] However, in the study, only three patients in MLS group and one in SOS group had evidence of small lacerations on the lip or oral mucosa. None of the four patients required further treatment, and all resolved within 24 h. These results might be related to the Cormack-Lehane classification applied in all patients before undergoing intubation and the extensive experience of the operator.…”
Section: Discussionmentioning
confidence: 76%
“…(90.0%) and Phua et al . (97.0%),[ 6 15 ] much higher than that for intubation by MLS (84.2%). Previous studies showed the risk of intubation failure at first attempt was approximately 15.0–35.0% with MLS in patients with increased risk for difficult tracheal intubation.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“… 28 29 Studies performed more recently suggested benefits from videolaryngoscopy but either failed to routinely use neuromuscular blockade, 8 29 in contradiction of current guidelines, or included patients with highly specific characteristics. 30 Furthermore, most studies of videolaryngoscopy were performed in the specific setting of difficult intubation 31 32 ( table 1 ).…”
Section: Introductionmentioning
confidence: 99%